ALKBH1 is a Histone H2A Dioxygenase Involved in Neural Differentiation123. (27th November 2012) - Ougland, Rune; Lando, David; Jonson, Ida; Dahl, John A.; Moen, Marivi Nabong; Nordstrand, Line M.; Rognes, Torbjørn; Lee, Jeannie T.; Klungland, Arne; Kouzarides, Tony; Larsen, Elisabeth
Abstract: AlkB homolog 1 (ALKBH1) is one of nine members of the family of mammalian AlkB homologs. Most Alkbh1 −/− mice die during embryonic development, and survivors are characterized by defects in tissues originating from the ectodermal lineage. In this study, we show that deletion of Alkbh1 prolonged the expression of pluripotency markers in embryonic stem cells and delayed the induction of genes involved in early differentiation. In vitro differentiation to neural progenitor cells (NPCs) displayed an increased rate of apoptosis in the Alkbh1 −/− NPCs when compared with wild‐type cells. Whole‐genome expression analysis and chromatin immunoprecipitation revealed that ALKBH1 regulates both directly and indirectly, a subset of genes required for neural development. Furthermore, our in vitro enzyme activity assays demonstrate that ALKBH1 is a histone dioxygenase that acts specifically on histone H2A. Mass spectrometric analysis demonstrated that histone H2A from Alkbh1 −/− mice are improperly methylated. Our results suggest that ALKBH1 is involved in neural development by modifying the methylation status of histone H2A. STEM CELLS 2012;30:2672–2682